Scrolling Scrolling, Watching, Buying: The Influence of TikTok User-Generated Content (UGC) Videos on Purchase Decisions through Customer Reviews of Eser Perfume Products - Allya Nihayah; Astri Wulandari; Riska Aprilina (Journal of Digital Marketing and Communication, 2026)
The emergence of TikTok as a social commerce platform has transformed the way consumers search for and evaluate products. This phenomenon is particularly interesting in the context of fragrance products (perfumes), as their primary attribute—the scent—cannot be experienced through a digital screen. Consequently, consumers face a unique challenge when making purchase decisions. Therefore, it is important to investigate how user-generated video content and customer reviews on TikTok influence consumers' purchasing decisions. This study aims to examine the effect of User-Generated Content (UGC) videos on TikTok on consumers' purchase decisions regarding Eser Perfume, with customer reviews serving as a mediating variable. An explanatory quantitative approach based on the Stimulus–Organism–Response (S–O–R) theory was employed. Data were collected through an online questionnaire administered to 200 active TikTok users in Indonesia selected using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that UGC videos have a positive and significant direct effect on purchase decisions (β = 0.659, p < 0.001) and strongly encourage consumers to read customer reviews (β = 0.890, p < 0.001). In addition, customer reviews positively influence purchase decisions (β = 0.310, p = 0.001) and serve as a partial mediating variable (indirect effect = 0.276). Overall, the proposed model explains 89.4% of the variance in purchase decisions (R² = 0.894). These findings suggest that organic TikTok videos influence consumers' perfume purchase decisions through two complementary mechanisms: direct visual appeal and the verification of product information through customer reviews. Accordingly, local perfume businesses are encouraged to optimize the creation of engaging UGC videos while maintaining the credibility and authenticity of customer reviews on TikTok to strengthen consumer trust and increase purchase intentions.